Peran dan Kontribusi Guru Mata Pelajaran Al-Qur’an Hadist Untuk Meningkatkan Kemampuan Menghafal Ayat-Ayat Al-Qur’an Pada Siswa Kelas VI Di MI Darussalam Kota Bengkulu 2018/2019 - Irhamna, Irhamna (GHAITSA : Islamic Education Journal, 2020)
The purpose of the study this is to find out what efforts the teacher of the Qur'an hadith in improving the ability to memorize the verses of the Qur'an in class VI students MI Darussalam 2018/2019 school year. This research uses a qualitative method with a descriptive approach. This research was conducted in MI Darussalam City of Bengkulu because there are characteristics namely the efforts of teachers of Al- Qur'an Hadith subjects in improving the ability to memorize verses of the Qur'an hadith. When the research was conducted from July 2018-January 2019. The subject of the research is the teacher of Al-Qur'an Hadith. The research informants were the Principal, Teachers besides the Qur'an Hadith, MI Darussalam Bengkulu City Students. Data collection method used are interviews, observation and documentation. To check The validity of the data uses data triangulation techniques from schools and sources know and relate to the efforts of teachers of the Qur'anic Hadith subjects in improving the ability to memorize the verses of al-quran .. Technical analysis using an interactive data analysis model, the steps taken are data reduction, presentation of data, and drawing conclusions or verification. From the results of the study it can be concluded that there are teacher efforts Al-Qur'an Hadith subjects to improve the ability to memorize Al-Qur'an verses in class VI MI Darussalam Bengkulu City. teacher effort The Qur'anic subjects of the Hadith include (1) Memorizing the Verses Al-Qur'an with the sima’i method. (2) Checking the Memorization of Al-Qur'an Verses. (3) students record the verses requested memorized, (4) Teachers Provide Motivation for students in memorization, (5) students are asked to write memorized verses, (6) The teacher provides assistance in memorizing the verses of the Al-Qur'an Hadith.